Pengaruh Word of Mouth (WOM) , Harga dan Lokasi Usaha terhadap Keputusan Wisatawan untuk Menginap di Grahita Suite Sanur - I Made Andika Naraditha; Anak Agung Istri Agung Maheswari; Putu Ratna Juwita Sari; Kadek Adyatna Wedananta (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
The rapid growth of tourism accommodation in Sanur has intensified competition among hotels, requiring managers to understand the key factors influencing tourists’ staying decisions. This study addresses the limited empirical evidence examining the combined role of Word of Mouth (WOM), price, and location in shaping accommodation choices, particularly for mid-scale hotels. The purpose of this research is to analyze the effects of WOM, price, and business location on tourists’ decisions to stay at Grahita Suite Sanur. A quantitative approach was employed using a survey method involving 108 tourists selected through accidental sampling. Data were collected through structured questionnaires and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results indicate that WOM, price, and location each have a positive and significant effect on tourists’ staying decisions. Simultaneously, these variables demonstrate a strong explanatory power in predicting accommodation choice. The findings highlight that credible recommendations, perceived price fairness, and strategic location are critical determinants of tourists’ decisions to stay. This study contributes to consumer behavior literature in tourism and provides practical insights for hotel managers in developing effective marketing strategies.